The Concept of Color Metaphor In Sundanese: A Semantic Cognitive Study - Muhammad Ivan Fauzi; Nurul Khasanah; Maria Dimitrij Angie Pavita (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2021)
This paper is a qualitative descriptive study that aims to describe the concept of color in Sundanese. In this study, the authors used the free-to-speak listening method without involving the participants. To support data collection, the author involves intuitive knowledge. In the method of analysis, the writer uses referential methods and semantic methods to describe and compare the relationship between metaphorical expressions as the source and the intended meaning of the target. The data taken are fragments of song lyrics, fragments of sentences from short stories, and proverbs. As a result, the authors found the colors hideung, beureum, bodas, konéng, héjo and blue in the concept of color as a Sundanese metaphor.Keywords: Metaphors, cognitive semantics, Sundanese language, conceptual metaphors